Hubungan antara Kualitas Pelayanan Karyawan Penyandang Disabilitas dengan Kepuasan Konsumen - Dea Nabila Fitri; Ani Yuningsih (UNISBA Press, 2023)
Abstract. The phenomenon of using the services of persons with disabilities at Café More is interesting to study because there tends to be a negative stigma for Café More. This research is important to examine because it can determine whether or not there is an influence of service quality of employees with disabilities on customer satisfaction. This study entitled